Eerie Elementary : The locker ate Lucy! - Book 2 Book 2 - Chabert, Jack; Ricks, Sam (New York : Branches/Scholastic Inc., 2014)
Only a week into his job as hall monitor and class protector, Sam Graves and his friends Lucy and Antonio are trying to uncover the secrets of Eerie Elementary, their living and malevolent school--and then Lucy gets eaten by her locker.
Keywords: Elementary schools -- Juvenile fiction; Best friends -- Juvenile fiction; Haunted schools -- Juvenile fiction; Rescues -- Juvenile fiction; Horror stories -- Juvenile fiction; Juvenile fiction